Fracture behavior of polypropylene fiber reinforced concrete modified by rubber powder exposed to elevated temperatures. (5th September 2022) - Zhou, Wenmei; Mo, Jinxu; Zeng, Lei; Xiang, Sheng
Highlights: Elevated temperature tests conducted on RPFC notched beams. Effect of different temperature on the fracture behavior of RPFC was studied. The damage evolution within the fracture process zone was monitored by AE and DIC. Fracture energy and fracture toughness first increase and then reduce with increasing temperature. Abstract: In this paper, the deterioration of fracture properties of rubber powder modified polypropylene fiber concrete (RPFC) after elevated temperatures is discussed. Three-point bending tests were conducted on 75 notched beams to discuss the effects of rubber powder content (0%, 5%, 10%, 15%), polypropylene fibers content (0%, 1%), and ambient temperature (25℃, 100℃, 200℃, 400℃, 600℃) on the fracture properties of RPFC. In addition, digital image correlation (DIC) techniques were used to measure crack development in RPFC notched beams. The fracture patterns, micro-crack initiation and extension and macro-crack development in the fracture process were identified using acoustic emission (AE) techniques. The results show that incorporating rubber powder into polypropylene fiber concrete can delay the crack propagation process, improve the deformation ability and make the fracture path more tortuous. With the rubber powder content increase from 5% to 15%, the initiation fracture toughness of RPFC notched beam decreased, the unstable fracture toughness and the fracture energy increased. When the ambient temperature rises from 25 ℃ to 600 ℃, the fracture energy and fracture toughness of RPFC increases first and then decreases, the crack mouth opening displacement increases, and ductility increases significantly. AE analysis further shows that the growth rate of accumulate counts decrease significantly with the rubber powder content in RPFC, indicating the rate of damage development has slowed down in some extent.